Implementation of a triage monitoring program for internal exposure to short-lived radionuclides in Israel—challenges and recommendations. (10th November 2021) - Shukrun, R H; Epstein, L; Koch, J; Benmaman, D; Buchbinder, L; Cohen, S; Veinguer, M; Datz, H
Abstract: Monitoring internal exposure to short-lived radionuclides is challenging, due to the frequent measurements required. ISO Standard 16 637 and the Swiss Personal Dosimetry Ordinance describe a screening measurement (triage monitoring) conducted in the workplace to identify workers suspected of internal exposure. Based on a previous study that examined the feasibility of using several commonly found radiation monitors in Israel in a triage monitoring program, we conducted a pilot study towards the implementation of triage monitoring in nuclear medicine facilities in Israel. The pilot study was conducted while considering the current Israeli regulations and local safety culture. We implemented the triage monitoring program in three nuclear medicine facilities in Israel, with a total of 55 monitored workers. The pilot study consisted of two stages: a short-term stage conducted in the largest manufacture of radiopharmaceuticals in Israel and a long-term stage in two nuclear medicine departments in Israel. During the first stage of the study, participants were asked to conduct a daily measurement at the end of the workday and send a urine sample to the national internal dosimetry laboratory. The second stage lasted 5 months in a major hospital and 18 months in a regional hospital. The workers were asked to perform the measurement at the end of the shift and send a urine sample if a defined threshold had been crossed. The mean participation rate in the long-term stage (>70%) indicates that implementation of the triage monitoring program could be successful in Israel. Based on the findings of the study, practical recommendations are listed: suitable monitoring devices, allocating a monitoring location, time of measurement, training of the workers, record keeping and coordination with a certified dosimetry laboratory. The pilot study recommendations were submitted to the Israel Institute for Occupational Safety and Hygiene at the Ministry of Labor, Social Affairs and Social Services.